Microplastics in the environment: Much ado about nothing? A debate - Backhaus, Thomas; Wagner, Martin (PeerJ Preprints, 2018)
This manuscript documents a debate between the two authors on the issue of microplastics in the environment. It was sparked by a recent viewpoint article published by G. A. Burton in Environmental Science and Technology (http://doi.org/10.1021/acs.est.7b05463) and started as a Twitter debate. To expand, we decided to continue our conversation publishing 1000-word texts on PeerJ and responding to each other in roughly two-week intervals. Currently, the text contains the following: 1) An introduction, which sets the scene for the article 2) Martin's kick-off statement “Soul-searching on microplastics: Lost in translation, prioritization and communication?”, dated Feb. 27, 2018 3) Thomas' opening statement “A genuine research topic, but let’s avoid hyperboles”, dated March 18, 2018 4) Martin’s rebuttal “Moving forward: What are the risks of microplastics?”, dated April 18, 2018 5) Thomas’ rebuttal “We need to do a classical risk assessment, but we can’t stop there”, dated May 18, 2018 6) Final statement of both authors, dated July 12, 2018
Keywords: Plastic pollution; Microplastics; microplastic; synthetic polymers; environmental risk assessment; anthropocene; precautionary principle